Analisis Peningkatkan Motivasi Belajar Melalui Penggunaan Media Interaktif Dalam Pembelajaran PAI Sekolah Dasar - Ayunda, Hasnirda; Fitriani, Wahidah (Innovative: Journal Of Social Science Research, 2024)
This study aims to analyze the use of interactive media in improving students' learning motivation in Islamic Religious Education (PAI) subjects in elementary schools. This study uses a qualitative research method with a literature review analysis technique to collect data and scientific information related to the research theme. The results of the study indicate that students' learning motivation is influenced by several factors, including relevant goals, a supportive environment, challenges and successes, and the role of teachers as the main source of motivation. Strategies that can improve students' learning motivation include, arousing interest, providing constructive feedback, building emotional bonds, and providing choices. The use of interactive media can also provide quick feedback on student performance, increasing motivation because students feel more confident when they see their progress. Thus, this study recommends the use of interactive media as an effective solution to improve students' learning motivation in Islamic Religious Education subjects in elementary schools. Keywords: Learning Motivation, Interactive Media, Elementary School PAI